Coumarin derivative as a potent drug candidate against triple negative breast cancer targeting the frizzled receptor of wingless-related integration site signaling pathway. Issue 5 (24th March 2023) - Uttarkar, Akshay; Kishore, Alice Preethi; Srinivas, Sudhanva M.; Rangappa, Shobith; Kusanur, Raviraj; Niranjan, Vidya
Abstract: Triple negative breast cancer constitutes to about 21.8 percent of the total breast cancer related cases. Its ability to affect young ladies and in pre-menstrual stage makes this a disease of concern worldwide. The current treatment regimens involve chemotherapy which are used for treatment of other cancer types. In this regard, there is a need for specific and targeted drug candidate for its effective treatment. In the current study, assessment of coumarin derivative 2-(2-(6- Methyl-2-Oxo-2H-chromen-4-yl) acetamido)-3-phenylpropanoic acid is carried out both In-silico and In-vitro methods. Frizzled transmembrane proteins of Wingless-related integration site signaling pathway was targeted in which Frizzled-7 proved to a prospective target and showed a binding energy of −6.78 kcal/mol. The complex was subjected to molecular dynamics simulation for 200 ns and showed stable interaction with cysteine rich domain of the receptor. Cell proliferation, viability and apoptosis assay were performed on MDA-MB-231 and MDA-MB-468 cell lines with an IC50 value of 81.23 and 84.68 µM, respectively. The results provide a drug candidate which is derivative of a natural compound with targeted TNBC inhibitory effect. Communicated by Ramaswamy H. Sarma Abstract : UF0001